Answer:
y = x² + 7x + 12
Step-by-step explanation:
Given the zeros x = - 4 and x = - 3, then the corresponding factors are
(x - (- 4) ) and (x - (- 3) ), that is
(x + 4) and (x + 3)
The function is then the product of its factors
y = (x + 4)(x + 3) ← expand using FOIL
= x² + 7x + 12
(10x+20y+10z)
Answer:
I think the answer is 40.
Step-by-step explanation:
Answer:
Step-by-step explanation:
to find midpoint of (x₁, y₁) & (x₂, y₂):
coordinate of midpoint =
Answer:
(15/2, 3) or (7.5, 3)
Step-by-step explanation:
To find the midpoint between two points, you can use the midpoint formula
midpoint =
In this case, the two points are (6, 2) and (9, 4).
So,
Now, plug these values into the formula:
Then, simplify.
So, the midpoint between the points (6, 2) and (9, 4) is or (7.5,3)
(I am never using equation again!)
Answer:
+9or -9 is the answer ☺️ you
Answer:
y will be equal to 0, 9, or 1
(y=0, 9, 1)
b.prism
c.pyramid eliminate
d.sphere?
Answer:
Step-by-step explanation: